KERAGAAN MORFO-FISIOLOGI SERTA KOMPONEN HASIL DAN HASIL GENOTIPE PADI PADA METODE BUDIDAYA TANAM BENIH LANGSUNG LAHAN BASAH - Rifqi Fauzi, Ahmad; Junaedi, Ahmad; Lubis, Iskandar; Ghulamhdi, Munif; Aswidinnoor, Hajrial (Politeknik Negeri Lampung., 2024)
The direct seeding of rice (DSR) system has been widely practiced in various Asian countries because it is considered more efficient in water and labor and provides better benefits than transplanting systems. However, improvements in the management of this system practice are still needed, especially in cropping patterns and the use of appropriate varieties. This study examines the physiological characteristics, yield components, and yields of rice genotypes in transplanting and DSR systems. This research was carried out in the field with transplanting and DSR cultivation systems (drill and broadcast sowing) and used four superior lines and one national variety. A total of 25 treatment combinations were designed using a split-plot randomized complete block design (Split plot-RCBD) with three replications for each treatment. The results showed that rice grown with DSR had no different level of greenery and photosynthesis rate than rice in transplanting cultivation, but produced lower panicle length, the number of grains per panicle, the number of filled grains, and faster flowering time. Genotype IPB193-F-17-2-3 produced the highest productivity in wet DSR (drill and broadcast sowing) and dry DSR (drill sowing). Genotype IPB193-F-38-2-1 had the highest productivity in transplanting techniques and dry DSR (broadcast method). The productivity of the Ciherang variety in the DSR system (drill method) was not different from the transplanting system. This finding indicates that the direct seeding system using the drill method is promising for further development.